Timing of Kidney Clamping and Deceased Donor Kidney Transplant Outcomes. Issue 11 (November 2021) - Ville, Simon; Lorent, Marine; Kerleau, Clarisse; Asberg, Anders; Legendre, Christophe; Morelon, Emmanuel; Buron, Fanny; Garrigue, Valérie; Le Quintrec, Moglie; Girerd, Sophie; Ladrière, Marc; Albano, Laetitia; et al.
Visual Abstract: Abstract : Background and objectives: The fact that metabolism and immune function are regulated by an endogenous molecular clock that generates circadian rhythms suggests that the magnitude of ischemia reperfusion, and subsequent inflammation on kidney transplantation, could be affected by the time of the day. Design, setting, participants, & measurements: We evaluated 5026 individuals who received their first kidney transplant from deceased heart-beating donors. In a cause-specific multivariable analysis, we compared delayed graft function and graft survival according to the time of kidney clamping and declamping. Participants were divided into those clamped between midnight and noon ( ante meridiem [am ] clamping group; 65%) or clamped between noon and midnight ( post meridiem [pm ] clamping group; 35%), and, similarly, those who underwent am declamping (25%) or pm declamping (75%). Results: Delayed graft function occurred among 550 participants (27%) with am clamping and 339 (34%) with pm clamping (adjusted odds ratio, 0.81; 95% confidence interval, 0.67 to 0.98; P =0.03). No significant association was observed between clamping time and overall death-censored graft survival (hazard ratio, 0.92; 95% confidence interval, 0.77 to 1.10; P =0.37). No significant association of declamping time with delayed graft function or graft survival was observed. Conclusions: Clamping between midnight and noon was associated with a lower incidence of delayed graft function, whereas declamping time was not associated with kidney graft outcomes.